Modernization of Relay Protection and Automation of Boston 110/35/10 KVL Power Supply, Supplying Pump Station with Power (Texas Journal of Engineering and Technology, 2022)
This article discusses the problem of developing new protection schemes and the use of digital and microprocessor relays in relay protection systems in substations during the modernization of protective devices of power transformers in the substation 110/35/10 kV Buston, which supply power energy of pump station.